Expert Novice Dialog (END) Di Masa Pandemi Covid-19 Untuk Menilai Kemampuan Komunikasi Sains: (Expert Novice Dialogue (END) During The Covid-19 Pandemic To Assess Science Communication Ability) - Evi Paojiah; Suhendar Suhendar; Gina Nuranti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
This study aims to determine the science communication skills of high school students are assessed using the Expert-Novice Dialog (END) method with the help of Google Suite. This research was conducted at one of the Sukabumi City Senior High Schools in April the second week of 2021. This study uses a descriptive method with a quantitative approach. The sampling technique used in this research is purposive sampling technique. The subjects used in this study were students of class X SMA, totaling 60 students consisting of 20 Experts and 40 Novices. Data collection were carried out digitally with the help of Google Suite. The concept of the selected material is a change in environmental balance. The instruments used in this research are science communication skills rubric, observation rubric, novice concept test and student response questionnaires. The results showed that the science communication skills of students in one of the Sukabumi City Senior High Schools were assessed using the Expert-Novice Dialog (END) method assisted by Google Suite an average of 67% which was included in the